2011
DOI: 10.1111/j.1099-0860.2010.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

The Everyday Costs of Poverty in Childhood: A Review of Qualitative Research Exploring the Lives and Experiences of Low-Income Children in the UK

Abstract: This review of 10 years of qualitative research with disadvantaged children in the UK shows that despite some gaps in the knowledge base, there is now a substantive body of evidence exploring children's lives and experiences from their own perspectives. The review reveals that poverty penetrates deep into the heart of childhood, permeating every facet of children's lives from economic and material disadvantage, through the structuring and limiting of social relationships and social participation to the most pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(148 citation statements)
references
References 21 publications
12
133
0
3
Order By: Relevance
“…Cross-sectional research has demonstrated that living in poverty influences children's health and wellbeing (Marmot, 2012;Ridge, 2011), and that accounting for the higher Anna Pearce, Steven Hope, Hannah Lewis, Catherine Law Family structure and socio-emotional wellbeing in the early years… rates of poverty in some family types reduces the association between family structure and child wellbeing (Pearce et al, 2013;Spencer, 2005). However, poverty can be fluid in nature (Graham & Power, 2004), and experiences of those who are exposed to persistent, rather than transient, poverty are likely very different (Bradshaw 2011a).…”
Section: Comparison With Other Findingsmentioning
confidence: 99%
“…Cross-sectional research has demonstrated that living in poverty influences children's health and wellbeing (Marmot, 2012;Ridge, 2011), and that accounting for the higher Anna Pearce, Steven Hope, Hannah Lewis, Catherine Law Family structure and socio-emotional wellbeing in the early years… rates of poverty in some family types reduces the association between family structure and child wellbeing (Pearce et al, 2013;Spencer, 2005). However, poverty can be fluid in nature (Graham & Power, 2004), and experiences of those who are exposed to persistent, rather than transient, poverty are likely very different (Bradshaw 2011a).…”
Section: Comparison With Other Findingsmentioning
confidence: 99%
“…Stigma has been described as "a special relationship between an attribute and stereotype," characterized by the discrepancy between someone's self-perception and the way he or she is perceived by others, and related to shame or discredit (Goffman, 1963). Here, the stigma lived by children was defined in different contexts, such as school and home; it has been previously reported that schools can be a "corrosive and damaging environment" for children living in poverty (Brabant et al, 2016;Ridge, 2011). Educators mentioned helping children navigating the social barriers they encountered in their daily lives by helping them develop their academic capacities.…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition to the troubling incidence of people (especially children) going without enough to eat and being hungry, food insecurity is associated with a wide range of serious health and developmental problems. 17 Rose-Jacobs and colleagues 18 found that even mild nutritional deficits during critical periods of brain growth cause harm to children’s physical, mental, social, and emotional health. The result is a cascade of permanent, lifelong negative consequences.…”
Section: Food Insecurity and Health Disparitymentioning
confidence: 99%